INTERACTING GRAVITATIONAL EXCITONS AND OBSERVABLE EFFECTS FROM EXTRA DIMENSIONS - Gunther, U.; Zhuk, A. I. (Одеські астрономічні публікації, 2017)
It is supposed that a multidimensional manifold undergoes a spontaneous compactification M -> M4xΠ ni=1Mi, where M4 is the 4 dimensional external space-time and Mi are compact internal spaces. Conformal excitations of the internal space metric can be observed as massive and massless scalar -fields (gravitational excitons) in the external space-time. Specific interaction features of gravitational excitons with gravitons are considered.